(untitled) (Eventum: A Journal of Medieval Arts & Rituals, 2023)
Focusing on the restoration of material culture associated with pilgrimages, the authors examine how a temporally distant period might be reanimated in the present – or, by contrast, retains potential to be animated but remains dormant. They compare two pilgrimage sites, both characterized by disruptive historical caesuras that define salient periods of destruction of valued eras from the past. In Walsingham (England), the key break is represented by the northern European Reformation. At this site, the medieval remains prominent in the present, where it is repeatedly re-enacted, though in the context of loss. In the Monastery of Apostolos Andreas (Cyprus), the significant caesura is more recent, referring to the de facto partition of Cyprus in 1974. Here, the fifteenth-century chapel contained within the site has not been translated into substantial signs of medieval presence or performance. Despite their differences, both cases studied in this paper demonstrate how a caesura designates the period to be recalled and given an ‘afterlife’.